Determinan Profitabilitas Bank : Studi Kasus Pada Bank Pembangunan Daerah - Ahmad, Gatot Nazir (Jurnal Keuangan dan Perbankan, 2015)
This research has purpose to analyze determinants that affect State Development Bankâs (BPD) profiitability. This research is inspired by Bank Decree, State Bank Regulation and State Autonomy Decree when doing ths research. By using panel data analysis, random effect, we find that almost all determinants have predicted sign accordingly and statistically significant.